2013
DOI: 10.1289/ehp.1205829
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorooctanoic Acid Exposure and Cancer Outcomes in a Contaminated Community: A Geographic Analysis

Abstract: Background: Perfluorooctanoic acid (PFOA) has been linked to cancer in occupational mortality studies and animal toxicologic research.Objective: We investigated the relationship between PFOA exposure and cancer among residents living near the DuPont Teflon-manufacturing plant in Parkersburg, West Virginia (WV).Methods: Our analyses included incident cases of 18 cancers diagnosed from 1996 through 2005 in five Ohio (OH) counties and eight WV counties. For analyses of each cancer outcome, controls comprised all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
191
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(204 citation statements)
references
References 19 publications
6
191
1
Order By: Relevance
“…Our findings for prostate cancer, non-hepatitis liver disease and male thyroid disease have some support in earlier work. Positive prostate cancer trends, generally of borderline significance, were found in Vieira et al 18 (ecological study in the mid-Ohio valley), Eriksen et al 19 (study in population with background PFOA levels), and Lundin et al 20 (study in population with occupational levels). Positive trends in male thyroid disease were found in our community/worker combined cohort study 13.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our findings for prostate cancer, non-hepatitis liver disease and male thyroid disease have some support in earlier work. Positive prostate cancer trends, generally of borderline significance, were found in Vieira et al 18 (ecological study in the mid-Ohio valley), Eriksen et al 19 (study in population with background PFOA levels), and Lundin et al 20 (study in population with occupational levels). Positive trends in male thyroid disease were found in our community/worker combined cohort study 13.…”
Section: Discussionmentioning
confidence: 91%
“…In humans, the primary associations that have been observed have included ulcerative colitis (an autoimmune disease),12 thyroid disease,13 high cholesterol,14 15 kidney cancer,16 17 testicular cancer,17 18 prostate cancer19 20 and non-malignant kidney disease 16. Pregnancy-induced hypertension has also been associated with PFOA 21…”
Section: Introductionmentioning
confidence: 99%
“…Concerning cancer, two papers concluded that there was a probable link between high PFOA exposure and testicular and kidney cancers, and, at the highest exposures, with non-Hodgkin lymphoma and prostate and ovarian cancers [305,306]. On the other hand, a strong inverse…”
Section: More Exposed Populationsmentioning
confidence: 99%
“…Chronic exposure to PFOA and PFOS causes tumors in experimental animals, but there are no chronic toxicology data for other PFAAs (Lau, 2012). PFOA has been described as a likely human carcinogen by USEPA Science Advisory Board (USEPA, 2006) and has been linked to two types of cancer in communities with drinking water exposure (Vieira et al, 2013). PFOA may also increase the risk of prostate cancer (Gilliland and Mandel, 1993).…”
Section: Introductionmentioning
confidence: 99%